Evaluación de la actividad antifúngica in vitro del marco (Ambrosia arborescens Mill.) y matico (Aristeguietia glutinosa Lam.) sobre hongos patógenos causantes de la dermatomicosis - Ayala Valarezo, Sandra Elizabeth (2014)
The strong trend toward natural, and the current ethnomedicinal practice in Ecuador, allows the study of species that can be used therapeutically, although empirical knowledge is priceless, is not enough, it’s essential to validate the presence of chemical substances which have antifungal, antibacterial, antiviral activity, with less pathological risk than conventional synthetic products. The investigation presents the evaluation of the antifungal activity of Ambrosia arborescens Mill (Marco) extract and Aristeguietia glutinosa Lam. (Matico) essential oil on dermatophytes, and also a comparison with a full-scale antifungal, Clotrimazole. Seven concentrations (100-700 ppm) of Ambrosia arborescens Mill extract and ten concentrations (0.5 to 5%) of Aristeguietia glutinosa Lam. EO, were evaluated over Trichophyton mentagrophytes, Trichophyton rubrum, Microsporum canis and Candida albicans, it has been used Dimethylsulfoxide (DMSO) as the negative target and Clotrimazole as the positive target, as the comparison parameters, also clotrimazole was considered to establish the relative percentage of inhibition.